Adrenal incidentaloma: subclinical Cushing's syndrome. - Newell-Price, J; Grossman, A (1996)
Adrenal incidentalomas present a significant differential diagnostic challenge. All patients with an incidentally discovered adrenal lesion should be carefully considered and re-evaluated to exclude extra-adrenal malignancy. Tumours with hypersecretory syndromes require excision, whilst those tumours more than 6 cm in size, particularly if they exhibit other features of malignancy on computed tomography (CT), magnetic resonance imaging (MRI) or scintigraphy, should also be excised. In all cases screening for phaeochromocytomas should be performed, and in the context of hypertension and spontaneous hypokalaemia, a primary aldosterone-secreting tumour requires exclusion. However, the natural history and treatment regimens for those individuals demonstrating 'subclinical Cushing's syndrome' is far from clear. Size, as determined by CT or MR scanning, does not in itself reliably distinguish benign from malignant disease. Scintigraphy may be a useful adjunct, with discordant patterns suggesting malignant disease. Fine needle aspiration should not routinely be used but may be useful in cases of doubt about other extra adrenal malignancy.